The efficacy of electronic health interventions targeting improved sleep for achieving prevention of weight gain in adolescents and young to middle‐aged adults: A systematic review. (10th February 2020) - Allman‐Farinelli, Margaret; Chen, Juliana; Chevance, Guillaume; Partridge, Stephanie R.; Gemming, Luke; Patrick, Kevin; Godino, Job G.
Summary: Sleep is emerging as a modifiable risk factor in counteracting harmful weight gain. Electronic and mobile devices offer a channel for wide‐reaching intervention delivery. This systematic review aimed to determine the efficacy of interventions that included sleep behaviour as part of health promotion for preventing weight gain. Seven databases were searched from 1 January 2000 until 28 June 2019. Eligible studies were controlled trials of weight gain prevention programs that addressed sleep in healthy participants aged 13 to 44 years of age. The primary outcome was change in measured or self‐reported weight. From 824 publications located, only six eligible trials with a total of 3, 277 participants were identified and all addressed multiple behaviours. One study demonstrated a decrease in weight for the intervention group, and two other studies showed a decreased prevalence of overweight and obesity. Only one trial showed improved sleep duration but failed to show differences in weight. No definitive conclusions concerning the efficacy of electronic weight gain prevention interventions that include sleep can be made, but future trials should provide more detail about intervention techniques used, employ objective sleep and physical activity measures and undertake mediation analysis to judge the contributions of changes in sleep to study outcomes. PROSPERO REGISTRATION: CRD42019121879.